PENERAPAN MODEL PEMBELAJARAN OPEN ENDED UNTUK MENINGKATKAN PEMAHAMAN KONSEP MATERI PERKALIAN DI SEKOLAH DASAR - Afni Putri, Dela; Fitra Surya, Yenni; Syahrul Rizal, Muhammad; Nurhaswinda; Sumianto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the low understanding of the concept of multiplication material in class III UPT SDN 009 Ganting, Salo District. One solution to overcome this problem is to apply the Open Ended learning model. The purpose of this study is to describe the improvement in understanding of the concept of multiplication material by applying the open ended learning model to class III students of UPT SDN 009 Ganting. The research method is Classroom Action Research (CAR) which is carried out in two cycles. Each cycle consists of two meetings and four stages, namely planning, implementation, observation, and reflection. The subjects of this study were 22 class III students, the number of male students was 11 people, and female students were 11 people. Data collection techniques were documentation, observation, and tests. Based on the results of data analysis, it can be seen that there was an increase in the understanding of the concept of multiplication material before the action, the average completeness of the reading comprehension skills was only 40.90 then in cycle I meeting I increased to 54.54, cycle I meeting II increased to 63.64. Furthermore, cycle II meeting I increased to 77.27 and cycle II meeting II increased to 90.90. So it can be concluded that the application of the open-ended learning model can improve the understanding of the concept of multiplication material in class III UPT SDN 009 Ganting.